Common random fixed point theorems for contractions of rational type in ordered metric spaces - Singh, Sukh Raj; daheriya, R D; Ughade, Manoj (International Journal of Advanced Mathematical Sciences, 2016)
In this paper, we prove some common random fixed point theorems for mappings involving rational expression in the framework of metric spaces endowed with a partial order using a class of pairs of functions satisfying certain assumptions.